Influence of Soil Properties on Methane Production Potential from Wetland Rice Field in Java - Setyanto, Prihasto (2000)
This study was conducted with the main objective of studying the emission and production potential of methane (CH4) from different soil types of wetland rice field and determining the controlling soil characteristics affecting methane production. The specific objectives are (i) to determine the best time in the day for manual sampling of CH4 gas in the field, (ii) to measure CH4 fluxes and total emission from three rice fields under field conditions, during the wet and dry seasons, and (iii) to determine the ability of some soils in Java to produce methane from its indigenous and added C source. Two experiments were conducted. The first was a field experiment. Three top soils, classified as brown Regosol, red Latosol and dark brown Alluvial, were placed in a wooden micro-plots lined with plastic sheets and planted with IR 64-rice variety. The soils received continuous irrigation with 5cm ponding above the soil throughout the growing season. A (l m x 1 m x 1 m) plexi-glass chamber was placed on each of the micro-plots to measure daily CH4 flux. The experiment was conducted for two seasons i.e. dry and wet seasons. The Eh and pH changes were recorded regularly every four days. Results of the experiment show that the emission of methane from the soils reached the highest peak at 40 days after transplanting (primordial stage). The emissions declined after they reached the early flowering stage, and drops to the lowest level until the plots were drained. There were no significant differences in grain yield between the three soils from two seasons of observation. Dark brown Alluvial (156. 1 kg CHJha/year) produced the highest emission followed by brown Regosol (142.2 kg CHJha/year) and red Latosol (39.6 kg CHJha/year). Reducing CRt emissions while maintaining or enhancing yield requires information on CRt fluxes from a wide range of ecosystems and climatic zones. An optimal less-intensive sampling strategy with the use of manually operated chamber to measure daily CRt flux is required. Result from this study suggests that gas sampling using the chamber at 1100 his the best time to represent the daily flux variation observed throughout the growing season.